Biomass-based ionic liquid modified carbon quantum dot and preparation method thereof, and composite lubricant
Through the preparation of biomass-based ionic liquid modified carbon quantum dots, the lack of performance of traditional petroleum-based lubricants under high temperature and high pressure conditions is solved, and efficient lubricants with environmental protection and long life are achieved. They are suitable for mechanical equipment, and It has environmentally friendly renewable characteristics.
Patent Information
- Application Number
- CN202411301482.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Traditional petroleum-based lubricants have limited lubrication performance, poor load-bearing capacity, and poor biodegradability under high temperature, high pressure, and easy-to-explosion conditions, resulting in shorter service life and environmental pollution.
Using biomass-based ionic liquid to modify carbon quantum dots, a lubricant with nanoballing effect is prepared by combining carbonized biomass raw materials, grinding, ultrasonic treatment, choline chloride and amino acid ionic liquids, to form a stable core-shell structure. , improve lubricating performance and durability, and improve dispersion and chemical bonding through choline amino acid ionic liquid modification of carbon quantum dots.
It achieves excellent lubricating performance, non-flammability, chemical stability and thermal stability under high temperature and high pressure conditions, extends the service life of the mechanical, reduces friction and wear, and monitors the service life of the lubricant through fluorescence, achieving environmental protection and cleaning Production goals.
Smart Images

Figure BDA0005047796670000091 
Figure HDA0005047796680000011 
Figure HDA0005047796680000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubricant development, and relates to a biomass-based ionic liquid modified carbon quantum dot and a preparation method thereof, and a composite lubricant. Background Art
[0002] With the rapid development of modern industry, mechanical equipment consumes most of its energy due to friction during operation, and the service life of mechanical parts is shortened. Therefore, lubricants are needed in mechanical movement. Lubrication is one of the important means to improve the friction state of friction pairs. Lubricants form a lubricating oil film on the friction surface, cut off the direct contact between the two friction surfaces, and reduce the friction and wear between the friction pairs, thereby saving energy and extending the service life of the machinery. At present, lubricants can be divided into solid lubricants, semi-solid lubricants and fluid lubricants. Among them, liquid lubricants belong to fluid lubricants, which are more widely used in practical applications. Among liquid lubricating materials, petroleum-based lubricants such as mineral oils have excellent lubricating properties, can effectively reduce the friction and wear of mechanical equipment, and increase the service life of equipment, so they are widely used in the industrial field.
[0003] However, with the substantial increase in mechanical power, traditional petroleum-based lubricants also have disadvantages such as low flash point and easy combustion under certain high temperature, high pressure, and explosive conditions, which are potentially dangerous. In addition, the lubricating performance of lubricants under such working conditions is limited, and the load-bearing capacity is poor, which greatly shortens their service life. Lubricants need to be added and replaced frequently, which increases production costs. At the same time, low biodegradability makes it easy to pollute the ecological environment after discharge, and the raw materials are non-renewable, which does not meet the country's requirements for green environmental protection. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a biomass-based ionic liquid modified carbon quantum dots and a preparation method thereof, and a composite lubricant, thereby solving the technical problems of the prior art petroleum-based lubricants in having limited lubrication performance and poor load-bearing capacity under high temperature, high pressure, explosive and other working conditions, as well as poor biodegradability.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing biomass-based ionic liquid modified carbon quantum dots comprises the following steps:
[0007] The biomass raw material is placed in an air atmosphere for carbonization and grinding, and the ground product is placed in water for ultrasonic treatment, and then the supernatant is obtained by centrifugation, and the supernatant is freeze-dried to obtain biomass carbon quantum dots;
[0008] Dissolving choline chloride and hydroxide base in anhydrous ethanol, stirring to react, to obtain choline hydroxide, and dropping the choline hydroxide aqueous solution into an amino acid aqueous solution, stirring to react, to obtain a choline amino acid ionic liquid;
[0009] The biomass carbon quantum dots are added to the choline amino acid ionic liquid, stirred and mixed evenly, and then a catalyst is added. After stirring for reaction, the product is vacuum freeze-dried to obtain the biomass-based ionic liquid modified carbon quantum dots.
[0010] Preferably, the biomass raw material is tea leaves or tea leaves residue; the tea leaves are one or more of black tea, green tea, dark tea, white tea, yellow tea or scented tea.
[0011] Preferably, the temperature during the carbonization process is 330-360° C. and the time is 2-4 hours.
[0012] Preferably, when the ground product is placed in water for ultrasonic treatment, the ratio of the ground product to water is (0.1-1):(10-100) by mass; when the supernatant is obtained by centrifugation, the centrifugal speed is 12000-18000 r / min.
[0013] Preferably, the hydroxide base is one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide or magnesium hydroxide; and the amino acid is one or more of citrulline, arginine, glutamic acid, glycine and alanine.
[0014] Preferably, the ratio of the choline chloride, the hydroxide base and the anhydrous ethanol is (10-20):(10-20):(120-150) by mass.
[0015] Preferably, in terms of mass fractions, the ratio of the biomass carbon quantum dots to the choline amino acid ionic liquid is (0.1-1):(1-10).
[0016] Preferably, the catalyst is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and / or 1-(3-dimethylaminopropylbenzene)-3-ethylcarbodiimide.
[0017] A biomass-based ionic liquid modified carbon quantum dot is prepared by the above method.
[0018] A composite lubricant, comprising the above-mentioned biomass-based ionic liquid modified carbon quantum dots; the friction coefficient of the composite lubricant is ≤0.1, and the wear rate is ≤1.90×10 -12 cm 3 / (N·m), fluorescence intensity ≥6.0×10 6 .
[0019] Compared with the prior art, the present invention has the following beneficial technical effects:
[0020] The present invention discloses a method for preparing biomass-based ionic liquid-modified carbon quantum dots, which first uses biomass raw materials to prepare carbon quantum dots, uses choline chloride, hydroxide base and amino acid to prepare ionic liquid, and finally uses choline amino acid ionic liquid to modify biomass carbon quantum dots to prepare biomass-based ionic liquid-modified carbon quantum dots (CQDs / ILs). The biomass carbon quantum dots prepared in the method have a unique quasi-spherical structure, and can function as "nano balls" when used as lubricants, changing the friction type between parts from sliding friction to rolling friction, thereby improving their load-bearing capacity and reducing wear. In addition, choline amino acid ionic liquid has good lubrication performance, non-flammability, good chemical stability and thermal stability. In addition to reducing friction, choline amino acid ionic liquid has good solubility. Using choline amino acid ionic liquid to modify carbon quantum dots can improve the dispersibility of tea carbon quantum dots on the one hand, and on the other hand, the amino group of choline amino acid ionic liquid interacts with the carboxyl group on the surface of carbon quantum dots to form a strong chemical bond, constructing a special chemically bonded core-shell structure, forming a stable "shell" structure on the surface of carbon quantum dots, further improving the tribological properties and lubrication durability. In addition, CQDs will emit blue fluorescence under ultraviolet light. When in use, the fluorescence intensity can be used to monitor the service life of the lubricant and whether there is leakage. Furthermore, the carbon quantum dots are prepared from biomass raw materials, and the choline chloride and amino acids of biomass are used to prepare choline amino acid ionic liquids. The raw materials have the advantages of wide distribution, abundant reserves, renewability and waste utilization. At the same time, the use of biomass renewable resources instead of traditional petrochemical resources to prepare carbon quantum dots and choline amino acid ionic liquids is environmentally friendly and can be decomposed by nature, achieving the concept of environmentally friendly chemistry, realizing clean production, and fundamentally eliminating environmental pollution, which is of great significance to the realization of the "dual carbon" goal. The present invention is convenient to prepare, has a reasonable process design, is green and environmentally friendly, and the obtained biomass-based ionic liquid modified carbon quantum dots have good high temperature resistance and lubrication performance, which has important theoretical value and practical significance for improving the lubrication performance and product service life of mechanical lubricants and expanding their scope of use.
[0021] Further, another inventive point of the present invention is that the biomass raw material is tea leaves or tea leaves residue; the tea leaves are one or more of black tea, green tea, dark tea, white tea, yellow tea or scented tea. First, tea leaves are rich in polyphenol compounds, amino acids and sugars, which can generate smaller and more uniform carbon quantum dots during pyrolysis and have good fluorescence properties. At the same time, the carbon content of tea leaves is relatively high, which enables it to produce more carbon quantum dots during pyrolysis. Tea leaves and their residues are by-products produced during tea production and are usually regarded as waste. However, these wastes are rich in organic matter and a variety of nutrients, which can be converted into valuable materials through reasonable use. Using tea leaves or tea leaves residues as biomass raw materials not only realizes the recycling of resources, but also reduces environmental pollution. The dispersibility, stability and functionality of biomass carbon quantum dots can be further improved through the modification of choline amino acid ionic liquids.
[0022] Further, another inventive point of the present invention is that the temperature in the carbonization process is 330-360°C and the time is 2-4h. First, within this temperature range, the organic components in the biomass raw materials can undergo moderate pyrolysis and carbonization reactions to generate carbonaceous materials with specific structures and properties. Too low a temperature leads to incomplete carbonization, while too high a temperature destroys the structure of the carbonaceous material and affects the performance of the final product. Secondly, the appropriate temperature helps to reduce the generation of impurities during the carbonization process. Too high a temperature will trigger unnecessary side reactions and generate impurities that are not conducive to subsequent applications. Within this temperature range, the reaction path can be better controlled to reduce the generation of impurities. Within this temperature range, the organic components in the biomass raw materials can be more effectively converted into carbonaceous particles, thereby increasing the yield of the product. The carbonization time is set to 2-4h, which can ensure that the organic components in the biomass raw materials are fully carbonized. A shorter time leads to incomplete carbonization, while a longer time increases energy consumption and cost, and may also trigger unnecessary side reactions. The appropriate carbonization time helps to optimize the structure of carbon quantum dots. Within this time range, the carbonaceous particles can form a more uniform and stable structure, thereby improving the performance of the product.
[0023] Further, another inventive point of the present invention is that when the ground product is placed in water for ultrasonic treatment, the ratio of the ground product to water is (0.1-1): (10-100) by mass; when the supernatant is taken by centrifugation, the centrifugal speed is 12000-18000r / min, wherein the appropriate ratio helps to evenly disperse the ground product in water, and too high a concentration of the ground product causes particle aggregation, affecting the effect of ultrasonic treatment; the appropriate ratio enables the ultrasonic wave to produce a more uniform and stronger cavitation effect in the suspension, thereby more effectively crushing and refining the ground product particles. High-speed centrifugation can generate a large centrifugal force, so that the large particles in the suspension quickly settle to the bottom of the centrifuge tube, thereby achieving the separation of larger solids and smaller quantum dots, which helps to obtain a pure, impurity-free biomass carbon quantum dot solution. Under the premise of ensuring the separation effect, a higher centrifugal speed can shorten the centrifugation time and improve the processing efficiency.
[0024] Furthermore, another inventive point of the present invention is that the hydroxide base is one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide or magnesium hydroxide; the amino acid is one or more of citrulline, arginine, glutamic acid, glycine and alanine. First of all, these hydroxide bases have strong alkalinity and can effectively react with raw materials such as choline chloride to generate corresponding choline hydroxide. These hydroxide bases have good solubility in solvents such as water and ethanol, which is conducive to the uniform reaction and purification of the product. Amino acids such as citrulline, arginine, glutamic acid, glycine and alanine have different structural and functional characteristics. After combining with choline, they can give ionic liquids different physical and chemical properties and biological activities. These amino acids are naturally occurring biomolecules with good biocompatibility and degradability.
[0025] Further, another inventive point of the present invention is that the ratio of choline chloride, hydroxide base and anhydrous ethanol is (10-20): (10-20): (120-150) by mass fraction, which ensures sufficient contact and mixing between the reactants, so that the reaction of choline chloride and hydroxide base can be carried out evenly, avoiding incomplete reaction or side reaction caused by excessively high or low local concentration, and the appropriate ratio of reactants helps to maximize the utilization of raw materials and reduce the residue of unreacted materials, thereby improving the yield of the product. Anhydrous ethanol, as a solvent, not only helps to dissolve and mix the reactants, but also can regulate the rate and selectivity of the reaction to a certain extent. An appropriate amount of anhydrous ethanol can also reduce side reactions that may occur during the reaction, such as hydrolysis, oxidation, etc., thereby protecting the structure and properties of the target product.
[0026] Furthermore, another inventive point of the present invention is that the ratio of the biomass carbon quantum dots to the choline amino acid ionic liquid is (0.1-1): (1-10) by mass. First, the amount of choline amino acid ionic liquid added is relatively large, which can effectively achieve effective modification of the surface of the biomass carbon quantum dots and improve the overall stability of the material. There is a synergistic effect between the biomass carbon quantum dots and the choline amino acid ionic liquid, that is, the combination of the two can produce better performance than when used alone. The appropriate ratio can maximize this synergistic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 This is a particle size diagram of tea carbon quantum dots (CQDs) prepared in Example 1 of the present invention;
[0029] Figure 2 TEM image of tea carbon quantum dots (CQDs) in Example 1 of the present invention;
[0030] Figure 3 The zeta potential diagrams of tea carbon quantum dots (CQDs), choline amino acid ionic liquids (ILs), and choline amino acid ionic liquid modified tea carbon quantum dots (CQDs / ILs) in Example 1 of the present invention;
[0031] Figure 4 This is a dispersion stability diagram of choline amino acid ionic liquid modified tea carbon quantum dots (CQDs / ILs) in water at different time points in Example 1 of the present invention;
[0032] Figure 5 This is a test graph of the friction coefficient of the composite lubricant modified with choline amino acid ionic liquid and tea carbon quantum dots (CQDs / ILs) added in water in different amounts in Example 1. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0035] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0036] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0038] The present invention provides a method for preparing biomass-based ionic liquid modified carbon quantum dots, which specifically comprises the following steps:
[0039] 1) Biomass Carbon Quantum Dots
[0040] First, 0.1 to 1 parts of biomass raw materials are placed in a muffle furnace and calcined at 330 to 360 ° C for 2 to 4 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product is crushed. Next, 0.1 to 1 parts of black solid powder are added to 10 to 100 parts of water for ultrasonic treatment for 1 to 3 hours. Finally, the upper layer solution is taken after high-speed centrifugation, and the upper layer solution is freeze-dried for 12 to 14 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0041] Wherein, the biomass raw material is tea leaves or tea leaves residue; the tea leaves are one or more of black tea, green tea, dark tea, white tea, yellow tea or scented tea. The rotation speed of the high-speed centrifuge is 12000-18000 r / min.
[0042] 2) Preparation of choline amino acid ionic liquid
[0043] First, 10 to 20 parts of choline chloride and 10 to 20 parts of hydroxide base are dissolved in 120 to 150 parts of anhydrous ethanol, stirred at 60 to 90°C for 6 to 8 hours, and after the reaction is completed, the anhydrous ethanol is removed by a rotary evaporator, and the product is choline hydroxide. Next, 10 to 30 parts of choline hydroxide are dissolved in 20 to 50 parts of water to obtain a choline hydroxide aqueous solution, and 0.1 to 1 part of an amino acid is dissolved in 40 to 400 parts of water at room temperature, and the above-obtained choline hydroxide aqueous solution is added dropwise to the amino acid aqueous solution, and after the addition is completed, the reaction is carried out at 50 to 90°C for 10 to 12 hours. After the reaction is completed, the water in the reaction solution is removed by reduced pressure distillation. Then, 100 to 200 parts of ethanol / acetonitrile (ratio) mixed solution is added to the distilled product and stirred for 1 to 2 hours and then allowed to stand for 0.5 to 1 hour to precipitate excess amino acids. Finally, the filtrate is separated by filtration, and the obtained filtrate is subjected to reduced pressure distillation to obtain a light yellow to yellow viscous liquid, and then dried in a vacuum oven at 70-100° C. for 6-8 hours to obtain a choline amino acid ionic liquid.
[0044] Wherein, the hydroxide base is one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, and magnesium hydroxide;
[0045] The amino acid is one or more of citrulline, arginine, glutamic acid, glycine and alanine.
[0046] In the dropping process, the dropping time of the choline hydroxide aqueous solution is 10 to 15 minutes.
[0047] The ethanol / acetonitrile mixture is calculated by weight, and the ratio of ethanol to acetonitrile is (10-100):(90-900).
[0048] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0049] First, 0.1 to 1 parts of tea carbon quantum dots (CQDs) and 1 to 10 parts of choline amino acid ionic liquids (ILs) are mixed and stirred evenly, and then 0.2 to 0.6 parts of catalyst are added thereto and stirred for reaction at 20 to 30° C. for 8 to 12 hours. After the reaction is completed, the reaction solution is vacuum freeze-dried for 10 to 14 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0050] The catalyst may be one or more of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) and 1-(3-dimethylaminopropylbenzene)-3-ethylcarbodiimide (EDC).
[0051] In addition, the present invention also discloses a biomass-based ionic liquid modified carbon quantum dot composite lubricant prepared by the above method. After testing, the friction coefficient of the lubricant prepared by the present invention is ≤0.1, and the wear rate is ≤1.90×10 -12 cm 3 / (N·m), fluorescence intensity ≥6.0×10 6 It can be seen that the biomass-based ionic liquid modified carbon quantum dot composite lubricant has excellent lubricity and wear reduction ability. After a series of variable load and variable frequency friction, the friction coefficient changes very little and still does not lose lubrication performance. The average friction coefficient of the lubricant refers to the ratio of the friction between the surfaces and the vertical force acting on the same surface under the action of a certain external force. The wear rate is the amount of wear of the material under a certain pressure within a certain period of time (or a certain stroke, each movement, etc.). The wear rate of this application is benchmarked against No. 45 steel, and a wear experiment is carried out under the conditions of 100N and 200r. The fluorescence intensity is the fluorescence intensity of the carbon quantum dot solution at an excitation wavelength of 380nm-800nm. The smoother the sliding surface, the smaller the friction coefficient, which is beneficial to energy saving and extending the life of the machine.
[0052] The present invention uses the MMUD-1B material ultra-high temperature friction and wear testing machine produced by Jinan Hengxu Testing Machine Technology Co., Ltd. to carry out friction and wear experiments. The material is 45# steel, the test conditions are 100N, 200r / min, end face friction pair, the measurement time is 1h, and the change curve of the friction coefficient over time is measured. Before each measurement, 1000 mesh sandpaper is used to grind the tinplate and the friction pair, and then wiped with acetone. The mass of the tinplate is weighed before and after the friction test, and its volume wear rate is calculated. The calculation formula is as follows:
[0053]
[0054] ω - volume wear rate, mm 3 / (N m);
[0055] m1—mass of the sample before testing, g;
[0056] m2—mass of the sample after testing, g;
[0057] ρ—density of the sample, g / mm 3 ;
[0058] L - sliding distance, m.
[0059] The invention discloses a method for preparing a biomass-based ionic liquid modified carbon quantum dot composite lubricant. The preparation method first prepares carbon quantum dots using biomass raw materials, then uses choline chloride and amino acids to prepare ionic liquids, and finally uses choline amino acid ionic liquids to modify biomass carbon quantum dots to prepare CQDs / ILs composite lubricants. Biomass tea carbon quantum dots are prepared using biomass raw materials, and choline amino acid ionic liquids are prepared using biomass choline chloride and amino acids. Tea carbon quantum dots and choline amino acid ionic liquid dots prepared using biomass renewable resources instead of traditional fossil energy are environmentally friendly and can be decomposed by nature, achieving the concept of environmentally friendly chemistry, realizing clean production, and fundamentally eliminating environmental pollution, which is of great significance to the realization of the "dual carbon" goal. Secondly, the unique quasi-spherical structure of tea carbon quantum dots (CQDs) can play the role of "nano ball" in CQDs / ILs composite lubricants, changing the friction type between parts from sliding friction to rolling friction, thereby reducing wear. Moreover, CQDs emit blue fluorescence under ultraviolet light, and the fluorescence intensity can be used to monitor the service life of the lubricant and whether it is leaking during use. Secondly, choline amino acid ionic liquid has good lubrication properties, non-flammability, good chemical stability and thermal stability. In addition to reducing friction, the choline amino acid ionic liquid itself has good solubility, and the choline amino acid ionic liquid is used to modify the biomass carbon quantum dots to not only improve the dispersibility of the biomass carbon quantum dots, but also to form a special core-shell structure with the biomass carbon quantum dots, further improving the tribological properties. In addition, the lubricant has the advantages of mild preparation process conditions, simple and easy control, low cost, and easy scale-up preparation.
[0060] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0061] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0062] Example 1
[0063] 1) Preparation of tea carbon quantum dots
[0064] First, 0.1 parts of Pu'er tea residues were placed in a muffle furnace and calcined at 330°C for 2 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 0.1 parts of the black solid powder was added to 10 parts of water for ultrasonic treatment for 1 hour. Finally, the upper layer solution was taken after high-speed centrifugation at 12000r / min, and the upper layer solution was freeze-dried for 12 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0065] 2) Preparation of choline amino acid ionic liquid
[0066] First, 10 parts of choline chloride and 10 parts of sodium hydroxide were dissolved in 120 parts of anhydrous ethanol, stirred at 60°C for 6 hours, and after the reaction was completed, the anhydrous ethanol was removed by a rotary evaporator, and the product was choline hydroxide. Next, 10 parts of choline hydroxide were dissolved in 20 parts of water to obtain a choline hydroxide aqueous solution, and 0.1 parts of citrulline were dissolved in 40 parts of water at room temperature. The above-obtained choline hydroxide aqueous solution was added dropwise to the citrulline aqueous solution within 10 minutes, and the reaction was carried out at 50°C for 10 hours after the dropwise addition. After the reaction was completed, the water in the reaction solution was removed by vacuum distillation. Then, 100 parts of ethanol / acetonitrile mixed solution were added to the distilled product and stirred for 1 hour and then stood for 0.5 hours to precipitate excess citrulline. Finally, the obtained filtrate was separated by filtration, and a light yellow to yellow viscous liquid was obtained by vacuum distillation, and then dried at 70°C for 8 hours in a vacuum oven to obtain a choline amino acid ionic liquid.
[0067] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0068] First, 0.1 parts of the prepared tea carbon quantum dots (CQDs) and 1 part of choline amino acid ionic liquid (ILs) were mixed and stirred evenly, and then 0.2 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride were added thereto and stirred for 8 hours at 20°C. After the reaction, the reaction solution was vacuum freeze-dried for 10 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0069] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added into water at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.1, the wear rate was 1.90×10 -12 cm 3 / (N·m), fluorescence intensity = 6.0×10 6 .
[0070] Figure 1This is a particle size diagram of tea carbon quantum dots (CQDs) prepared in Example 1 of the present invention. It can be seen from the figure that its hydration dynamic size is about 2nm, the distribution range of its peak is narrow, the particle size is uniform, and the stability is good.
[0071] Figure 2 This is the TEM image of the tea carbon quantum dots (CQDs) in Example 1 of the present invention. It can be seen from the figure that the CQDs sample is composed of evenly dispersed small dots, showing a spherical or quasi-spherical morphology. When used as a lubricant, it can effectively convert sliding friction into rolling friction, thereby improving lubrication efficiency.
[0072] Figure 3 This is the zeta potential diagram of tea carbon quantum dots (CQDs), choline amino acid ionic liquids (ILs) and choline amino acid ionic liquid modified tea carbon quantum dots (CQDs / ILs) in Example 1 of the present invention. Under normal circumstances, the higher the Zeta potential value, the more stable the system. It can be seen from the figure that the absolute value of the potential of the CQDs / ILs composite filler of this patent is 37.9mV, indicating that the composite filler has good stability in water.
[0073] Figure 4 This is a dispersion stability diagram of the choline amino acid ionic liquid modified tea carbon quantum dots (CQDs / ILs) in water at different time points in Example 1 of the present invention. It can be seen from the figure that CQDS / ILS can be evenly dispersed in water, and no precipitation occurs after 24 hours of standing, which shows that CQDS / ILS has good stability in water.
[0074] Figure 5 The friction coefficient test diagram is a test diagram of adding different amounts of the choline amino acid ionic liquid modified tea carbon quantum dots (CQDs / ILs) composite lubricant in Example 1 to water. Compared with pure water, the friction coefficient of the water-based lubricant added with the CQDs / ILs composite lubricant is reduced, reaching the lowest when the addition amount is 0.3wt%. This is mainly because during the friction process, CQDs and ILs can play a synergistic lubricating role, thereby forming a continuous, uniform, dense, and firm self-lubricating transfer film on the surface of the metal friction pair, effectively preventing the direct contact between the friction pair and the wear part, and reducing friction.
[0075] Example 2
[0076] 1) Preparation of tea carbon quantum dots
[0077] First, 1 part of Pu'er tea residue was placed in a muffle furnace and calcined at 360°C in an air atmosphere for 4 hours to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 1 part of the black solid powder was added to 100 parts of water for ultrasonic treatment for 3 hours. Finally, the upper layer solution was taken after high-speed centrifugation at 18000r / min, and the upper layer solution was freeze-dried for 14 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0078] 2) Preparation of choline amino acid ionic liquid
[0079] First, 20 parts of choline chloride and 20 parts of sodium hydroxide are dissolved in 150 parts of anhydrous ethanol, stirred at 90°C for 8 hours, and after the reaction is completed, the anhydrous ethanol is removed by a rotary evaporator, and the product is choline hydroxide. Next, 30 parts of choline hydroxide are dissolved in 50 parts of water to obtain a choline hydroxide aqueous solution, and 1 part of arginine is dissolved in 400 parts of water at room temperature. The above-obtained choline hydroxide aqueous solution is added dropwise to the arginine aqueous solution within 15 minutes, and the reaction is carried out at 90°C for 12 hours after the dropwise addition. After the reaction is completed, the water in the reaction solution is removed by vacuum distillation. Then, 200 parts of ethanol / acetonitrile mixed solution are added to the distilled product and stirred for 2 hours and then allowed to stand for 1 hour to precipitate excess arginine. Finally, the obtained filtrate is separated by filtration, and the obtained filtrate is subjected to vacuum distillation to obtain a light yellow to yellow viscous liquid, and then dried in a vacuum oven at 100°C for 6 hours to obtain a choline amino acid ionic liquid.
[0080] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0081] First, 1 part of the prepared tea carbon quantum dots (CQDs) and 10 parts of choline amino acid ionic liquids (ILs) were mixed and stirred evenly, and then 0.2 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride were added thereto and stirred for 12 hours at 0°C. After the reaction, the reaction solution was vacuum freeze-dried to obtain a choline amino acid ionic liquid modified tea carbon quantum dots composite lubricant.
[0082] First, 0.1 parts of the prepared tea carbon quantum dots (CQDs) and 1 part of choline amino acid ionic liquid (ILs) were mixed and stirred evenly, and then 0.2 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride were added thereto and stirred for 8 hours at 20°C. After the reaction, the reaction solution was vacuum freeze-dried for 14 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0083] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added into water at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.04, the wear rate was 1.20×10-12 cm 3 / (N·m), fluorescence intensity = 12.0×10 6 .
[0084] Example 3
[0085] 1) Preparation of tea carbon quantum dots
[0086] First, 0.2 parts of Zhengshan Xiaozhong tea residues were placed in a muffle furnace and calcined at 340°C for 3 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 0.2 parts of the black solid powder was added to 30 parts of water for ultrasonic treatment for 2 hours. Finally, the upper layer solution was taken after high-speed centrifugation at 15000r / min, and the upper layer solution was freeze-dried for 13 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0087] 2) Preparation of choline amino acid ionic liquid
[0088] First, 15 parts of choline chloride and 15 parts of potassium hydroxide were dissolved in 130 parts of anhydrous ethanol, stirred at 70°C for 7 hours, and after the reaction was completed, the anhydrous ethanol was removed by a rotary evaporator, and the product was choline hydroxide. Next, 15 parts of choline hydroxide were dissolved in 25 parts of water to obtain a choline hydroxide aqueous solution, and 0.2 parts of glutamic acid were dissolved in 90 parts of water at room temperature. The choline hydroxide aqueous solution obtained above was added dropwise to the glutamic acid aqueous solution within 11 minutes, and reacted at 60°C for 11 hours after the dropwise addition. After the reaction was completed, the water in the reaction solution was removed by vacuum distillation. Then, 120 parts of ethanol / acetonitrile mixed solution were added to the distilled product and stirred for 1.5 hours and then stood for 0.5 hours to precipitate excess amino acids. Finally, the obtained filtrate was separated by filtration, and a light yellow to yellow viscous liquid was obtained by vacuum distillation, and then dried in a vacuum oven at 80°C for 7 hours to obtain a choline amino acid ionic liquid.
[0089] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0090] First, 0.2 parts of the prepared tea carbon quantum dots (CQDs) and 3 parts of choline amino acid ionic liquids (ILs) were mixed and stirred evenly, and then 0.3 parts of 1-(3-dimethylaminopropylbenzene)-3-ethylcarbodiimide (EDC) were added thereto and stirred for 9 hours at 25°C. After the reaction, the reaction solution was vacuum freeze-dried for 11 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0091] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added into water at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.08 and the wear rate was 1.30×10-12 cm 3 / (N·m), fluorescence intensity = 8.0×10 6 .
[0092] Example 4
[0093] 1) Preparation of tea carbon quantum dots
[0094] First, 0.3 parts of Biluochun tea residues were placed in a muffle furnace and calcined at 350°C for 3 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 0.3 parts of black solid powder was added to 40 parts of water for ultrasonic treatment for 2 hours. Finally, the upper layer solution was taken after high-speed centrifugation at 15000r / min, and the upper layer solution was freeze-dried for 12 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0095] 2) Preparation of choline amino acid ionic liquid
[0096] First, 17 parts of choline chloride and 17 parts of potassium hydroxide were dissolved in 140 parts of anhydrous ethanol, stirred at 80°C for 7 hours, and after the reaction was completed, the anhydrous ethanol was removed by a rotary evaporator, and the product was choline hydroxide. Next, 20 parts of choline hydroxide were dissolved in 30 parts of water to obtain a choline hydroxide aqueous solution, and 0.4 parts of glycine were dissolved in 200 parts of water at room temperature. The choline hydroxide aqueous solution obtained above was added dropwise to the glycine aqueous solution within 12 minutes, and the reaction was carried out at 70°C for 11 hours after the dropwise addition. After the reaction was completed, the water in the reaction solution was removed by vacuum distillation. Then, 130 parts of ethanol / acetonitrile mixed solution were added to the distilled product and stirred for 1.5 hours and then stood for 0.8 hours to precipitate excess glycine. Finally, the obtained filtrate was separated by filtration, and a light yellow to yellow viscous liquid was obtained by vacuum distillation, and then dried at 80°C in a vacuum oven for 6.5 hours to obtain a choline amino acid ionic liquid.
[0097] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0098] First, 0.3 parts of tea carbon quantum dots (CQDs) and 3 parts of choline amino acid ionic liquids (ILs) were mixed and stirred evenly, and then 0.3 parts of 1-(3-dimethylaminopropylbenzene)-3-ethylcarbodiimide (EDC) were added thereto and stirred for 10 hours at 28°C. After the reaction, the reaction solution was vacuum freeze-dried for 12 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0099] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added into water at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.06 and the wear rate was 1.40×10 -12 cm 3 / (N·m), fluorescence intensity = 8.5×10 6 .
[0100] Example 5
[0101] 1) Preparation of tea carbon quantum dots
[0102] First, 0.4 parts of Xinyang Maojian tea residues were placed in a muffle furnace and calcined at 350°C for 2.5 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 0.4 parts of black solid powder was added to 40 parts of water for ultrasonic treatment for 2.5 hours. Finally, the upper layer solution was taken after high-speed centrifugation at 16000r / min, and the upper layer solution was freeze-dried for 13 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0103] 2) Preparation of choline amino acid ionic liquid
[0104] First, 16 parts of choline chloride and 16 parts of calcium hydroxide were dissolved in 140 parts of anhydrous ethanol, stirred at 75°C for 7 hours, and after the reaction was completed, the anhydrous ethanol was removed by a rotary evaporator, and the product was choline hydroxide. Then, 20 parts of choline hydroxide were dissolved in 40 parts of water to obtain a choline hydroxide aqueous solution, and 0.4 parts of alanine were dissolved in 220 parts of water at room temperature, and the above-obtained choline hydroxide aqueous solution was added dropwise to the alanine aqueous solution within 12 minutes, and reacted at 80°C for 10 hours after the addition was completed. After the reaction was completed, the water in the reaction solution was removed by vacuum distillation. Then, 150 parts of ethanol / acetonitrile mixed solution were added to the distilled product and stirred for 1.2 hours and then stood for 0.5 hours to precipitate excess alanine. Finally, the obtained filtrate was separated by filtration, and a light yellow to yellow viscous liquid was obtained by vacuum distillation, and then dried at 90°C for 7 hours in a vacuum oven to obtain a choline amino acid ionic liquid.
[0105] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0106] First, 0.4 parts of tea carbon quantum dots (CQDs) and 4 parts of choline amino acid ionic liquids (ILs) were mixed and stirred evenly, and then 0.5 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride were added thereto and stirred for 11 hours at 27°C. After the reaction, the reaction solution was vacuum freeze-dried for 13 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0107] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added into water at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.05, the wear rate was 1.50×10 -12 cm 3 / (N·m), fluorescence intensity = 9.0×10 6 .
[0108] Example 6
[0109] 1) Preparation of tea carbon quantum dots
[0110] First, 0.5 parts of Longjing tea residues were placed in a muffle furnace and calcined at 340°C for 3 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 0.5 parts of black solid powder was added to 50 parts of water for ultrasonic treatment for 2.5 hours. Finally, the upper layer solution was taken after high-speed centrifugation at 14000r / min, and the upper layer solution was freeze-dried for 12 to 14 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0111] 2) Preparation of choline amino acid ionic liquid
[0112] First, 15 parts of choline chloride and 15 parts of magnesium hydroxide are dissolved in 14 parts of anhydrous ethanol, stirred at 80°C for 7.5 hours, and after the reaction is completed, the anhydrous ethanol is removed by a rotary evaporator, and the product is choline hydroxide. Next, 20 parts of choline hydroxide are dissolved in 50 parts of water to obtain a choline hydroxide aqueous solution, and 0.1 to 1 part of glutamic acid is dissolved in 40 to 400 parts of water at room temperature, and the above-obtained choline hydroxide aqueous solution is added dropwise to the glutamic acid aqueous solution within 12 minutes, and reacted at 70°C for 12 hours after the addition is completed. After the reaction is completed, the water in the reaction solution is removed by vacuum distillation. Then, 150 parts of ethanol / acetonitrile (ratio) mixed solution is added to the distilled product and stirred for 1.5 hours and then allowed to stand for 0.5 hours to precipitate excess glutamic acid. Finally, the obtained filtrate is separated by filtration, and a light yellow to yellow viscous liquid is obtained by vacuum distillation, and then dried at 85°C in a vacuum oven for 6.5 hours to obtain a choline amino acid ionic liquid.
[0113] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0114] First, 0.5 parts of the prepared tea carbon quantum dots (CQDs) and 6 parts of choline amino acid ionic liquids (ILs) were mixed and stirred evenly, and then 0.3 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride were added thereto and stirred for 10 hours at 25°C. After the reaction, the reaction solution was vacuum freeze-dried for 12 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0115] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added to PAO-10 synthetic oil at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.045 and the wear rate was 1.70×10 - 12 cm 3 / (N·m), fluorescence intensity = 8.5×10 6 .
[0116] Example 7
[0117] 1) Preparation of tea carbon quantum dots
[0118] First, 0.8 parts of Tieguanyin tea residues were placed in a muffle furnace and calcined at 360°C for 2 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 0.8 parts of black solid powder was added to 80 parts of water for ultrasonic treatment for 1.5 hours. Finally, the upper layer solution was taken after high-speed centrifugation at 16000r / min, and the upper layer solution was freeze-dried for 12 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0119] 2) Preparation of choline amino acid ionic liquid
[0120] First, 19 parts of choline chloride and 19 parts of sodium hydroxide were dissolved in 145 parts of anhydrous ethanol, stirred at 85 ° C for 7.5 hours, and after the reaction was completed, the anhydrous ethanol was removed by a rotary evaporator, and the product was choline hydroxide. Then, 25 parts of choline hydroxide were dissolved in 45 parts of water to obtain a choline hydroxide aqueous solution, and 0.8 parts of arginine were dissolved in 300 parts of water at room temperature. The above-obtained choline hydroxide aqueous solution was added dropwise to the amino acid aqueous solution within 14 minutes, and reacted at 80 ° C for 12 hours after the addition was completed. After the reaction was completed, the water in the reaction solution was removed by vacuum distillation. Then, 180 parts of ethanol / acetonitrile (ratio) mixed solution was added to the distilled product and stirred for 2 hours and then stood for 1 hour to precipitate excess arginine. Finally, the obtained filtrate was separated by filtration, and a light yellow to yellow viscous liquid was obtained by vacuum distillation, and then dried at 80 ° C for 8 hours in a vacuum oven to obtain a choline amino acid ionic liquid.
[0121] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0122] First, 0.8 parts of the prepared tea carbon quantum dots (CQDs) and 8 parts of choline amino acid ionic liquids (ILs) were mixed and stirred evenly, and then 0.5 parts of 1-(3-dimethylaminopropylbenzene)-3-ethylcarbodiimide were added thereto and stirred for 11 hours at 28°C. After the reaction, the reaction solution was vacuum freeze-dried for 13 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0123] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added to PAO-10 synthetic oil at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.41 and the wear rate was 1.30×10 -12 cm 3 / (N·m), fluorescence intensity = 9.5×10 6 .
[0124] Example 8
[0125] 1) Preparation of tea carbon quantum dots
[0126] First, 0.6 parts of oolong tea residues were placed in a muffle furnace and calcined at 350°C for 3 hours in an air atmosphere to obtain a dark black solid product, and then the dark black solid product was crushed. Next, 0.6 parts of black solid powder was added to 60 parts of water for ultrasonic treatment for 3 hours. Finally, the upper layer solution was taken after high-speed centrifugation at 15000r / min, and the upper layer solution was freeze-dried for 14 hours to obtain a light yellow powder, which is tea carbon quantum dots.
[0127] 2) Preparation of choline amino acid ionic liquid
[0128] First, 14 parts of choline chloride and 14 parts of potassium hydroxide are dissolved in 140 parts of anhydrous ethanol, stirred at 70 ° C for 7 hours, and after the reaction is completed, the anhydrous ethanol is removed by a rotary evaporator, and the product is choline hydroxide. Then, 24 parts of choline hydroxide are dissolved in 40 parts of water to obtain a choline hydroxide aqueous solution, and 0.6 parts of citrulline are dissolved in 350 parts of water at room temperature. The above-obtained choline hydroxide aqueous solution is added dropwise to the citrulline aqueous solution in 12 minutes, and the reaction is carried out at 70 ° C for 10 hours after the dropwise addition. After the reaction is completed, the water in the reaction solution is removed by vacuum distillation. Then, 140 parts of ethanol / acetonitrile (ratio) mixed solution is added to the distilled product and stirred for 1 hour and then allowed to stand for 0.5 hours to precipitate excess citrulline. Finally, the obtained filtrate is separated by filtration, and a light yellow to yellow viscous liquid is obtained by vacuum distillation, and then dried at 90 ° C for 7 hours in a vacuum oven to obtain a choline amino acid ionic liquid.
[0129] 3) Preparation of choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant
[0130] First, 0.6 parts of the prepared tea carbon quantum dots (CQDs) and 6 parts of choline amino acid ionic liquids (ILs) were mixed and stirred evenly, and then 0.5 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride were added thereto and stirred for 10 hours at 25°C. After the reaction, the reaction solution was vacuum freeze-dried for 12 hours to obtain a choline amino acid ionic liquid modified tea carbon quantum dot composite lubricant.
[0131] The obtained biomass-based ionic liquid modified carbon quantum dot composite lubricant was added to PAO-10 synthetic oil at a minimum ratio of 0.2wt% for tribological performance testing. The results showed that the friction coefficient was 0.047 and the wear rate was 1.70×10 - 12 cm 3 / (N·m), fluorescence intensity = 7.5×10 6 .
[0132] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing biomass-based ionic liquid modified carbon quantum dots, characterized in that: The following steps are involved: The biomass raw material is placed in an air atmosphere for carbonization and grinding, and the ground product is placed in water for ultrasonic treatment, and then the supernatant is obtained by centrifugation, and the supernatant is freeze-dried to obtain biomass carbon quantum dots; Dissolving choline chloride and hydroxide base in anhydrous ethanol, stirring to react, to obtain choline hydroxide, and dropping the choline hydroxide aqueous solution into an amino acid aqueous solution, stirring to react, to obtain a choline amino acid ionic liquid; The biomass carbon quantum dots are added to the choline amino acid ionic liquid, stirred and mixed evenly, and then a catalyst is added. After stirring for reaction, the product is vacuum freeze-dried to obtain the biomass-based ionic liquid modified carbon quantum dots.
2. The method for preparing biomass-based ionic liquid-modified carbon quantum dots according to claim 1, characterized in that: The biomass raw material is tea leaves or tea leaves residue; the tea leaves are one or more of black tea, green tea, dark tea, white tea, yellow tea or scented tea.
3. The method for preparing biomass-based ionic liquid-modified carbon quantum dots according to claim 1, characterized in that: The temperature during the carbonization process is 330-360° C. and the time is 2-4 hours.
4. The method for preparing biomass-based ionic liquid-modified carbon quantum dots according to claim 1, characterized in that: When the ground product is placed in water for ultrasonic treatment, the ratio of the ground product to water is (0.1-1):(10-100) by weight; when the supernatant is obtained by centrifugation, the centrifugal speed is 12000-18000 r / min.
5. The method for preparing biomass-based ionic liquid modified carbon quantum dots according to claim 1, characterized in that: The hydroxide base is one or more of potassium hydroxide, sodium hydroxide, calcium hydroxide or magnesium hydroxide; the amino acid is one or more of citrulline, arginine, glutamic acid, glycine and alanine.
6. The method for preparing biomass-based ionic liquid modified carbon quantum dots according to claim 1, characterized in that: In terms of mass fractions, the ratio of the choline chloride, hydroxide base and anhydrous ethanol is (10-20):(10-20):(120-150).
7. The method for preparing biomass-based ionic liquid modified carbon quantum dots according to claim 1, characterized in that: Calculated by weight, the ratio of the biomass carbon quantum dots to the choline amino acid ionic liquid is (0.1-1):(1-10).
8. The method for preparing biomass-based ionic liquid modified carbon quantum dots according to claim 1, characterized in that: The catalyst is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and / or 1-(3-dimethylaminopropylbenzene)-3-ethylcarbodiimide.
9. A biomass-based ionic liquid modified carbon quantum dots, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. A composite lubricant, characterized in that: The composite lubricant comprises a biomass-based ionic liquid modified carbon quantum dots as described in claim 9; the friction coefficient of the composite lubricant is ≤0.1, and the wear rate is ≤1.90×10 -12 cm 3 / (N·m), fluorescence intensity ≥6.0×10 6 .
Citation Information
Patent Citations
Polydopamine nanosphere / boron nitride quantum dot / graphene solid lubricant, and preparation method, application and composite material thereof
CN113861679A
Carbon quantum dot with ionic liquid structure as well as preparation method and application of carbon quantum dot
CN114149332A
Preparation method of biomass carbon quantum dot / polyimide lubricating composite material
CN114410217A
Preparation method of anion modified carbon quantum dots as lubricating oil additive
CN114574198A
Lubricant composition containing ionic liquid and method for realizing super lubrication
CN118028042A
Cited By
Anti-counterfeiting film and preparation method thereof
CN119875256A
High-performance concrete and preparation method thereof
CN120365022A
